How civilizations die (and why Islam is dying too) - Goldman, David P. (Regnery Pub. ; Distributed to the trade by Perseus Distribution, 2011)
Thanks to collapsing birthrates, much of Europe is on a path of willed self-extinction. But birthrates in Muslim nations are declining faster--at a rate never before documented. Europe may have the resources to support an aging population, if at a terrible economic and cultural cost. But in the impoverished Islamic world, an aging population means a civilization on the brink of total collapse. Muslim decline poses new threats to America, challenges we cannot face effectively without a wholly new kind of political analysis that explains how desperate peoples and nations behave. David P. Goldman--author of the celebrated "Spengler" column--reveals how massive shifts in global power are remaking our future: how extinctions of peoples, cultures, and civilizations are not unthinkable, but certain; how for the first time in world history, the birthrate in the West has fallen below replacement level; why birthrates in the Muslim world are falling even faster; why the "Arab Spring" is the precursor of much more violent change in the Islamic world; why looming demographic collapse may encourage Islamic terrorists to "go for broke;" and how the United States can survive the coming world turmoil.--From publisher description.